The role of technology in the real estate industry - Warburton, Dale (Department of Construction Economics and Management, 2017)
The global real estate industry is said to be five years behind the technology curve. By some estimates, as much as a third of global real estate assets are managed by spreadsheets. Despite this, venture capital firms around the globe invested $1.5bn in real estate technology during 2015 and a further $1.8bn in the first half of 2016 (CB Insights, 2016). Within that context, this research seeks to examine whether or not real estate companies leverage technology to achieve best value, what the major benefits of technology are and finally, the key inhibiting and enabling factors impacting technology adoption. Initially, a theoretical foundation of modern facilities management is laid, including its relationship to real estate. An examination of the most prominent broad and specific technologies follows. A qualitative approach was favoured, specifically, a case study combined with semi-structured interviews of information technology leaders in the global real estate industry. It was established that real estate companies do leverage technology to achieve best value, but that the degree, nature and extent thereof varies depending on a range of systemic, idiosyncratic and external factors. It was established that the most significant benefits of technology were operational efficiencies and remote accessibility of real-time operational data. The key enabling factors were found to be robust, affordable infrastructure, the consumerisation of technology, scale and technology-focused leadership. The absence of these factors were regarded as having an inhibitory impact.